The potential effect of fatty acids from Pliek U on epidermal fatty acid binding protein: chromatography and bioinformatic studies - Nanda Earlia,; Rahmad, Rahmad; Mohamad Amin,; Prakoeswa, Crs; Khairan, Khairan; Idroes, Rinaldi (Penerbit Universiti Kebangsaan Malaysia, 2019)
The fatty acid analysis in Pliek U and its bioinformatic studies had been carried out and reported. Herein, fatty acids were analyzed by gas chromatography-mass spectrometry (GC-MS), meanwhile their potential effect, based on its interaction on epidermal fatty acid binding protein (E-FABP), was studied by bioinformatics approach with reverse docking technique using palmitic acid as a control compound. For the stated purpose, two Pliek U extracts were prepared, namely ethanolic Pliek U extract (EPUE), and ethanolic of residue hexane of Pliek U extract (ERHPUE). The GC-MS results showed that lauric, myristic, palmitic, and oleic acids were predominant, followed by stearic, capric, linoleic, and caprylic acids. Reverse docking results showed that linoleic acid had the lowest binding affinity (-5.9 kcal/mol) and was strongly bound to E-FABP on the same side of amino acid GLN A98, ARG A81, TYR A22, and LYS A61. These findings indicated that linoleic acid has a potential utility as a drug candidate for atopic dermatitis treatment.